Optimalisasi Biaya dan Jarak Transportasi Galon Air pada Depot Air Isi Ulang Cakra RO dengan Menggunakan Metode North West Corner dan Stepping Stone - Sasongko, Dimas Fauzan Aji; Mahmud, Mahmud; Rizkijanto, Damar (CV. ULIL ALBAB CORP, 2025)
The problem that arises at the Cakra RO Refill Depot is that the company has not been able to meet all consumer demand evenly and on time, delays in the arrival of products to consumers often occur, if left unchecked it will make consumers move to other products that is cheaper and easier to get on the market, so that the company will suffer a big loss. In the final assignment of optimizing the distribution of bottled drinking water which is designed to optimize the distribution of drinking water using the North West Corner and Stepping Stone methods at the Cakra RO Refill Depot, the NWC Method is a method that allocates products based on factory capacity and consumer needs which are small in value, while the Stepping Stone Method is a method that aims to minimize distribution costs from source to destination by looping continuously until the value resulting from the multiplication of product allocation and costs is positive, so that minimum distribution costs are obtained. This Final Assignment aims to facilitate companies in the process of distributing goods from source to destination at minimum cost.